DSA plus TCMR Leads to Poor Outcomes in Renal Allograft Recipients and this is Markedly Exacerbated by Non-Adherence. (July 2018) - Chittka, Dominik; Cherukuri, Aravind; Sharma, Akhil; Mehta, Rajil; Hariharan, Sundaram; Rothstein, David M.
Abstract : Introduction: Post-transplant DSA is strongly associated with poor renal allograft outcomes but has limited predictive value. In this prospective study, we aimed to risk-stratify patients with early post-transplant DSA to allow timely identification of individuals at-risk for poor clinical outcomes. Methods: Patients were screened for DSA at 0, 1, 3, 6, 9 & 12 months and analyzed in relation to protocol biopsies at 3 and 12 months and any for-cause biopsies within the first year. Results: 294/372 patients transplanted between 01/2013 and 11/2014 with at least one biopsy in the first post-transplant year were included in the analysis. The immunosuppressive regimen was Thymoglobulin induction followed by MPA and Tacrolimus as maintenance therapy. 67/294 (22.8%) of these patients developed DSA. Of these, 76% were detected within the first 3 months with 58% being persistent. DSA was associated with significantly increased rates of subclinical and clinical TCMR (58%) compared to patients lacking DSA (33%; p<0.0001). Importantly, presence of DSA was associated with higher Banff grade TCMR (Fig. 1A) and with a higher rate of concomitant AMR (10.4% vs. 1.8%, p=0.003). In 77% of patients with both DSA and TCMR, DSA was detected at the same time or prior to TCMR. Patients with DSA and TCMR had significantly worse chronic allograft histological changes at 1 year (Fig. 1B) and significantly increased graft loss or impending graft loss (eGFR<30ml/min with >30% decline from baseline) at 4 years when compared to the others, including patients with TCMR or DSA alone (Fig. 1C). In a multivariate Cox model, younger recipient age, Class I HLA mismatch, DGF and poor adherence (defined by a high intra-patient CNI variability (>35%)) were independently associated with DSA plus TCMR. Of these, non-adherence, which is potentially modifiable, further risk stratified patients with DSA plus TCMR. In fact, >70% of nonadherent patients with DSA plus TCMR have already lost their grafts or showed impending graft loss by 4 years, whereas patients with DSA plus TCMR who were adherent had outcomes relatively comparable to the other patient groups (Fig. 1D). Conclusion: Thus, early post-transplant DSA is associated with increased TCMR which in turn leads to poor graft outcomes, particularly in nonadherent patients. Strategies to address non-adherence in patients with DSA plus TCMR should be explored to improve long-term graft outcomes. Deutsche Forschungsgesellschaft (DFG). American Society of Transplantation (AST). Figure. No caption available.